STRATEGI PENDIDIK DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA MENGGUNAKAN MEDIA VIDEO PEMBELAJARAN PADA MAPEL AL-QUR’AN HADIS DI KELAS VIII MTSs ASY SYARIF SIDANG KOTO LAWEH - Yulia Sri Yan; Ulva Rahmi; Ali Amran (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This research aims to identify and analyze the effectiveness of strategies implemented by educators in increasing students' learning motivation through the use of learning video media in the Al-Qur'an Hadith subject in class VIII MTs Asy Syarif Sidang Koto Laweh. The research method used is classroom action research by observing and recording learning activities over two cycles. The research results show that implementing this strategy can significantly increase student learning motivation. Educators use learning video media carefully and creatively to explain concepts in Al-Qur'an Hadith subjects. Students show more active and enthusiastic participation in learning, which is reflected in improved test results and engagement in class discussions. In addition, the results of interviews and questionnaires showed that students responded positively to the use of learning video media, stating that it made learning more interesting and made it easier for them to understand the lesson material. Therefore, it can be concluded that this strategy is effective in increasing students' learning motivation in the Al-Qur'an Hadith subject in class VIII MTs Asy Syarif Sidang Koto Laweh. The implications of this research can be used as a reference for educators and researchers in developing innovative and interesting learning methods for similar subjects at the secondary education level.